SVZonChip: a paradigm shift in hydrocephalus research and treatment - Ioannis Angelopoulos (Exploration of Neuroscience, 2025)
Congenital hydrocephalus (CH) is an extreme cerebrospinal fluid (CSF) condition that affects brain development. Current medical treatments, such as ventriculoperitoneal shunting and endoscopic third ventriculostomy, are invasive and susceptible to complications. The subventricular zone (SVZ) is involved in CH, but investigations are hindered by conventional models. Here, we introduce SVZonChip, a dynamic 3D microfluidic device simulating SVZ physiology and CSF dynamics, presenting a proof-of-concept system that could be applied for studying CH. This bioengineered device provides a translational bridge between disease modeling and therapeutic discovery, opening up avenues for non-invasive treatments.